State-Permeated Capitalism and the Solar PV Industry in China and India. Issue 4 (4th July 2021) - Allen, Matthew M. C.; Allen, Maria L.; Saqib, Syed Imran; Liu, Jiajia
ABSTRACT: Much of the existing business and management research on how 'state capitalism' influences industry outcomes focuses on the state as 1) the owner of companies, 2) a provider of key resources, such as financial support, to favoured companies and/or 3) a unitary actor. Whilst some of this literature highlights links between politicians and officials, on the one hand, and individual companies, on the other, it downplays how other political-economic factors, such as the relative importance of existing industries in terms of employment and links between state banks and state-owned companies impact developments within those emerging sectors that the state wishes to promote. Drawing on the 'state-permeated model' of capitalism, we undertake a comparative institutional analysis of the development of the solar photovoltaic (PV) industry in China and India. Both states prioritised domestic solar PV manufacturing and innovation; however, China's industry is much stronger than India's, reflecting, we argue, 1) the greater ability of China's central state to co-ordinate other actors and 2) the greater importance of India's coal industry compared to China's. We discuss the implications of our work for policy makers and for research, highlighting the need to assess whether state-permeated capitalism is functional or dysfunctional in nuanced ways.